Growth and Relation of Private Savings and Gross Domestic Product in Bosnia and Herzegovina. Issue 5 (3rd September 2018) - Vladušić, Ljubiša; Dragović, Vaso; Bašić, Dragana
Abstract: Private savings cannot be observed separately from investments in economic theory. There is a relation between the growth of private savings and the growth of gross domestic product (GDP). In transition countries such as Bosnia and Herzegovina (BH), the growth of foreign direct investment (FDI) is in the function of the growth of GDP which, is to a lower extent, applicable for the growth of domestic private savings. In the long-term perspective, economic recovery of these countries should rely on investments through domestic private savings and capital accumulation, as it ensures economic independence and stability of every state. The development base of BH's economy since 1998 has mainly been based on the policy of attracting foreign investment, through either loans arrangements and foreign direct investments FDIs. This article presents the results of research focused on the growth of private savings and GDP and their relation in BH in the period from 1998 to 2015. The research has been conducted on the basis of data published by official domestic and international organizations (Statistics Agency, banks, International Monetary Fund, the World Bank and others). The purpose of the research is to obtain information on the growth tendencies and the strength of the relation of these two aggregates in the mentioned period, which is important for the creation and realization of economic policy.